Patu™: Fighting fit, fighting fat! The Hinu Wero approach. (September 2016) - Forrest, Rachel; Taylor, Lee-Anne; Roberts, Jennifer; Pearson, Maria; Foxall, Donna; Scott-Chapman, Sue
The PATU ™ Aotearoa Hinu Wero (Fat Challenge) is a group exercise initiative that promotes physical activity and focuses on fat loss in order to reduce obesity in Māori. This study evaluated the effectiveness of the pilot nine-week Hinu Wero (August–October 2014) involving 66 participants (males n = 26, females n = 40, ages 17–63 years) using a mixed-methods approach. Pre-and post-Hinu Wero anthropometric data revealed whether changes in body fat percentage, body mass index, and weight occurred. Mean reductions in all these measurements were observed. An online focus group with 13 of the participants, and a trainer interview (n = 1, male, 28 years) was undertaken in June 2015 to obtain various perspectives of the Hinu Wero. The online focus group participants were very enthusiastic about the PATU ™ Hinu Wero and the results being achieved. It was acknowledged that the Māori practice of whanaungatanga (connectedness, support) was of paramount importance. The PATU ™ Hinu Wero functioned as an effective health intervention for reducing obesity in local Māori and working towards reducing health inequities in New Zealand.